Migration and the wage curve: a structural approach to measure the wage and employment effects of migration - Herbert Brücker; Elke J. Jahn (Institute for the Study of Labor (IZA), 2008)
Based on a wage curve approach we examine the labor market effects of migration in Germany. The wage curve relies on the assumption that wages respond to a change in the unemployment rate, albeit imperfectly. This allows one to derive the wage and employment effects of migration simultaneously in a general equilibrium framework. For the empirical analysis we employ the IABS, a two percent sample of the German labor force. We find that the elasticity of the wage curve is particularly high for young workers and workers with a university degree, while it is low for older workers and workers with a vocational degree. The wage and employment effects of migration are moderate: a 1 percent increase in the German labor force through immigration increases the aggregate unemployment rate by less than 0.1 percentage points and reduces average wages by less 0.1 percent. While native workers benefit from increased wages and lower unemployment, foreign workers are adversely affected.
urn:nbn:de:101:1-2008040189
Keywords: F22; 330; Migration; wage curve; labor demand; panel data; Einwanderung; Migranten; Lohnkurve; Lohnstruktur; Arbeitsnachfrage; Arbeitslosigkeit; Panel; Deutschland